2022
DOI: 10.20452/pamw.16227
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical characteristics of hospitalized heart failure patients with a reduced, mildly reduced and preserved ejection fraction

Abstract: The definition of heart failure (HF) phenotypes is relatively new. There is scarce evidence on the true characteristics of patients with HF in the Polish population, which are classified into three categories. The presented study provides a broad characterization of the relevant phenotypes of patients hospitalized for HF. Furthermore, the information retrieved from the electronic database was validated for the diagnosis of HF, which makes a significant difference compared to studies based on the electronic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
(99 reference statements)
9
12
0
Order By: Relevance
“…Compared with HFrEF, patients with HFmrEF or HFpEF were older, more commonly women, with more atrial brillation, but less ischemic heart disease. These differences in the clinical pro le between HF subgroups have also been observed by others [19,20,[28][29][30]. As these differences may have an impact on the clinical course of patients with HF, it is important to ascertain whether HCRU and healthcare costs may vary according to the type of HF, as well.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Compared with HFrEF, patients with HFmrEF or HFpEF were older, more commonly women, with more atrial brillation, but less ischemic heart disease. These differences in the clinical pro le between HF subgroups have also been observed by others [19,20,[28][29][30]. As these differences may have an impact on the clinical course of patients with HF, it is important to ascertain whether HCRU and healthcare costs may vary according to the type of HF, as well.…”
Section: Discussionsupporting
confidence: 55%
“…Although some studies have analyzed the clinical pro le and management of HF strati ed by EF (HFrEF, HF with mildly reduced EF [HFmrEF] and HFpEF) [19][20][21], there are very few studies that have focused on identifying cost drivers according to HF phenotype [22][23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, patients with HFrEF had more atherosclerotic cardiovascular disease. Other studies have some similar differences in the clinical profile, except for hypertension, which is usually more common among patients with HFpEF [ 19 , 20 , 24 , 25 , 36 ]. In fact, ischemic heart disease and hypertension are the most common causes of HFrEF and HFpEF, respectively [ 1 ].…”
Section: Discussionmentioning
confidence: 84%
“…Data from 1061 Japanese patients (median age 81 years) showed that 61% had HFpEF and 39% had HFrEF [ 24 ]. In another study that analyzed 2601 hospitalized HF patients (mean age 64 years), 62% had HFrEF, 25% had HFpEF, and 13% had HFmrEF [ 25 ]. Although some studies have reported that half of all patients with HF have HFpEF, all these data indicate that the prevalence of HFpEF is markedly associated with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation